PERLINDUNGAN TAMAN NASIONAL KERINCI SEBLAT DALAM KAITANNYA DENGAN PEMBANGUNAN BERKELANJUTAN - Salfutra, Reko Dwi (Fakultas Hukum Universitas Bangka Belitung, 2016)
Kerinci Seblat National Park (TNKS) is a conservation area which the rich in biodiversity that has been recognized internationally as a World Heritage Site. Based the Act Number 41 of 1999 years, that the supervision of TNKS implemented by the government while respecting the indegineous people. However, TNKS protection is often overlooked. There are many problems in to the protection the TNKS, such as illegal logging, burning and destruction of the ecosystem in the TNKS area. Cause of that, goverment mush be to make the rule about the protection of TNKS with the suistanable development concept.